Effect of Leadership Style and Job Satisfaction on Employee Performance: Evidence from Indonesia Honorary Staff - Rusmewahni, Rusmewahni; Jayanti, Suci Etri; Siahaan, Rumiris; Sinurat, Mangasi; Ilham, Rico Nur (Indonesia Academia Research Society, 2024)
This study investigates the impact of leadership style and job satisfaction on employee performance within the General Section of the Regional Secretariat of the Serdang Bedagai Regency. Multiple linear regression analysis was employed to examine the relationships between variables using questionnaires, interviews, and literature reviews for data collection. The findings reveal that leadership style in a department is categorized as high or good, significantly influencing employee performance. It aligns with the theoretical expectation that appropriate leadership is crucial for enhancing employee performance, particularly when performance declines. Surprisingly, contrary to expectations, job satisfaction was classified as low and did not significantly affect employee performance. The study concludes that leadership style and job satisfaction are well received in the General Section, as evidenced by their highly descriptive classification. These factors collectively and simultaneously influence employees’ performance. This research recommends addressing and fulfilling employees’ needs to improve job satisfaction and potentially impact performance. This study contributes to understanding Human Resource Management practices in a specific organizational context by highlighting the importance of effective leadership and the need for strategies to enhance job satisfaction. These findings provide valuable insights for managers and policymakers in developing targeted interventions to improve employee performance in similar organizational settings.